2021
DOI: 10.1080/17405629.2020.1865143
|View full text |Cite
|
Sign up to set email alerts
|

Gender role identity and gender intensification: Agency and communion in adolescents’ spontaneous self-descriptions

Abstract: In line with gender stereotypes, girls are expected to take on communal roles and boys to take on agentic roles. Based on gender intensification theory, the present cross-sectional study investigated girls' and boys' gender role identity and corresponding age differences across adolescence using the spontaneous self-description method. In total, 3423 adolescents aged between 11 and 15 years were asked to describe themselves with three attributes later coded in terms of agency and communion. ANOVA results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 78 publications
2
15
0
2
Order By: Relevance
“…Regarding the contextual factor in learning, our results have shown higher perceived teacher support among girls than among boys. While previous studies on ICT did not find differences between boys and girls in perceived teacher expectations and support (Vekiri, 2010), this finding is not surprising given the stronger orientation toward social relationships and social support in the feminine gender role associated with girls compared to the masculine gender role associated with boys in Western societies (Helgeson, 1994;Korlat et al, 2021). In line with gender stereotypes, previous studies showed that girls rely more upon social support, especially in difficult or stressful situations (Helsen et al, 2000;Tamres et al, 2002), which might have been the case for digital learning during COVID-19.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Regarding the contextual factor in learning, our results have shown higher perceived teacher support among girls than among boys. While previous studies on ICT did not find differences between boys and girls in perceived teacher expectations and support (Vekiri, 2010), this finding is not surprising given the stronger orientation toward social relationships and social support in the feminine gender role associated with girls compared to the masculine gender role associated with boys in Western societies (Helgeson, 1994;Korlat et al, 2021). In line with gender stereotypes, previous studies showed that girls rely more upon social support, especially in difficult or stressful situations (Helsen et al, 2000;Tamres et al, 2002), which might have been the case for digital learning during COVID-19.…”
Section: Discussionmentioning
confidence: 69%
“…Accordingly, by the time of adolescence, boys report higher frequency of computer use and greater self-confidence in dealing with computers (Colley and Comber, 2003;Mucherah, 2003), display greater digital skills (Kayany and Yelsma, 2000;Li and Kirkup, 2007), and in general are more attracted to computers than girls (Mumtaz, 2001;Volman and van Eck, 2001;Colley and Comber, 2003). Similarly, it has been found that boys describe themselves in relation to computers (e.g., "computer freak" or "I like computers") significantly more often than girls (Korlat et al, 2021). Newer studies support the finding that computer use for both education and entertainment purposes is more frequent among boys (Drabowicz, 2014).…”
Section: Gender Differences In Stereotyped Domainsmentioning
confidence: 98%
“…Additionally, people perceive communion, which includes traits such as sensitivity and patience, to be more characteristic of women (Eagly et al, 2020). Other constructs described as masculinity and femininity respectively are instrumentality, which refers to action and self-confidence (Spence & Helmreich, 1980), and expressiveness (Spence et al, 1974), which refers to an awareness of the emotions of others and kindness (Korlat et al, 2021;Spence & Helmreich, 1980). Such descriptors can be used to capture both impressions of others and groups as a whole, as in research on gender stereotypes, but can also be related to how one perceives oneself, in the form of attribute self-perceptions (Tobin et al, 2010).…”
Section: Gender Role Self-conceptsmentioning
confidence: 99%
“…Estos resultados apuntan a una evolución de los roles tradicionales de género que se han estudiado a otras redes sociales como YouTube e Instagram (Linares-Bahillo, Aristegui-Fradua y Beloki-Marañón, 2019; Regueira, Alonso-Ferreiro y Da-Vila, 2020; Ye, et al, 2018). Nuestros resultados sugieren que los y las adolescentes en esta red social muestran comportamientos similares en relación a los contenidos que producen y difunden dando lugar al desvanecimiento de sus diferencias de género, en consonancia con las investigaciones de van Oosten y Vandenbosch (2017) que confirman la igualdad de género en las representación estereotipadas de adolescentes en las redes sociales y de Korlat, et al (2021) que descubren más similitudes que diferencias de género en las autodescripciones que los adolescentes realizan de sí mismos en la redes sociales.…”
Section: Conclusiones Y Discusiónunclassified